Development of a reference standard for the detection and quantification of Mycobacterium avium subsp. paratuberculosis by quantitative PCR - Beinhauerova, Monika; Beinhauerova, Martina; McCallum, Sarah; Sellal, Eric; Ricchi, Matteo; O'Brien, Rory; Blanchard, Beatrice; Slana, Iva; Babak, Vladimir; Kralik, Petr (Scientific reports, 2021)
Quantitative PCR (qPCR) has become a frequently employed direct method for the detection and quantification of Mycobacterium avium subsp. paratuberculosis (MAP). The quantity of MAP determined by qPCR, however, may be affected by the type of qPCR quantification standard used (PCR product, plasmid, genomic DNA) and the way in which standard DNA quantity is determined (absorbance, fluorescence). In practice, this can be reflected in the inability to properly compare quantitative data from the same qPCR assays in different laboratories. Thus, the aim of this study was to prepare a prototype of an international MAP reference standard, which could be used to calibrate routinely used qPCR quantification standards in various laboratories to promote clinical data comparability. Considering stability, storage and shipment issues, a lyophilised fecal suspension artificially contaminated with a MAP reference strain was chosen as the most suitable form of the standard. The effect of five types of lyophilisation matrices on standard stability was monitored on 2-weeks interval basis for 4 months by F57 qPCR. The lyophilisation matrix with 10% skimmed milk provided the best recovery and stability in time and was thus selected for subsequent comparative testing of the standard involving six diagnostic and research laboratories, where DNA isolation and qPCR assay procedures were performed with the parallel use of the identical supplied genomic DNA solution. Furthermore, the effect of storage conditions on the standard stability was tested for at least 6 months. The storage at room temperature in the dark and under light, at + 4 °C, - 20 °C and - 80 °C showed no significant changes in the stability, and also no substantial changes in MAP viability were found using phage amplification assay. The prepared MAP quantification standard provided homogeneous and reproducible results demonstrating its suitability for utilisation as an international reference qPCR standard.
Keywords: Mycobacterium avium subsp. paratuberculosis; senzitivita a specificita; nemoci skotu; kvantitativní polymerázová řetězová reakce; Paratuberculosis; Animals; Real-Time Polymerase Chain Reaction; Feces; Sensitivity and Specificity; Freeze Drying; referenční standardy; Reference Standards; zvířata; DNA bakterií; Cattle; skot; DNA, Bacterial; lyofilizace; feces; Cattle Diseases; paratuberkulóza